THE EFFECT OF NEGATIVE EARNINGS TOWARDS VALUE RELEVANCE OF ACCOUNTING NUMBERS - B. Linggar Yekti Nugraheni (Department of Management - Faculty of Business and Economics. Universitas Surabaya., 2011)
This study investigates the volatility in the value-relevance of earnings and book values of equity over the last 10 years in Indonesia. The study uses statistical association between stock prices and accounting numbers represented by earnings and book values of equity. This study addresses 3 main questions. First, how is the value relevance of the earnings and book value of equity. Second, how is the volatility pattern of value relevance of earnings and book value of equity. Third, how is the effect of negative earnings towards value relevance of the earnings and book value of equity. The sample used in this research are public companies listed in Indonesia Stock Exchange (IDX). The samples generated during the observation periods are 1860 companies listed in IDX. This study reports five primary findings. First, earnings and book value of equity, jointly and individually, have significant explanatory power for securities prices over the last 10 years. Second, the combined value-relevance of earnings and book values has increased over time. Third, the incremental value-relevance of book value of equity has increased over time while that of earnings has declined. Fourth, for companies which report negative earnings, book value of equity was not evidenced to have greater value relevance compared to earnings. Fifth, the frequencies of negative earnings is associated with the change of value relevance of earnings and book value of equity.